Odpowiedzi

2010-01-06T17:21:33+01:00
-2(z-4)+5(z-4)=-2z+8+5z-20=3z-12

(a-1)²-(2a-1)²+2(a-2)(a+2)=a²-2a+1-(4a²-4a+1)+2a²-8=a²-2a+1-4a²+4a-1+2a²-8=-a²+2a

(-z-y)²-4<ra*zy>(3x-2)(-2-3x)=z²+y²-2zy-4*(-6z-9x²+4+6x)=z²+y²-2zy+24z+36x²-16-24x

2010-01-06T17:39:09+01:00
-2(z-4)+5(z-4)=-2z+8+5z-20=3z-12


(a-1)*-(2a-1)*+2(a-2)(a+2)=(a*-2a+1)-(4a*-4a+1)+2(a-2)* =(a*-2a+1)-(4a*-4a+1)+2(a*-4+4=(a*-2a+1)-(4a*-4a+1)+2a*-8+8=a*-2a+1-4a*+4a-1+2a*-8+8=-a*+2a


(-z-y)*-4<razy>(3x-2)(-2-3x)=
z*-2zy+y*-4<razy>(3x-2)(-3x-2)=
z*-2zy+y*-4<razy>(-9x*-6x+6x+4)=
z*-2zy+y*+36x*+24x-24-16=
z*-2zy+y*+36x*+24x-40

* => do potegi